2019
DOI: 10.1101/802181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Embryonic organoids recapitulate early heart organogenesis

Abstract: Organoids are powerful models for studying tissue development, physiology, and disease. However, current culture systems disrupt the inductive tissue-tissue interactions needed for the complex morphogenetic processes of native organogenesis. Here we show that mouse embryonic stem cells (mESCs) can be coaxed to robustly undergo the fundamental steps of early heart organogenesis with an in vivo-like spatiotemporal fidelity. These axially patterned embryonic organoids support the generation of cardiovascular prog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These have proven immensely useful to measure contraction force, perform compound screens and model structural muscle and arrhythmogenic disorders. Similarly, mouse and human PSC-derived 3D cardiac models including spherical aggregates (microtissues) of CMs and other cardiac cell types (Giacomelli et al, 2017;Richards et al, 2020), have been reported as promising tools for drug discovery; and embryoid models (Rossi et al, 2019;Silva et al, 2020) as providing insights into germ layer interactions in early organogenesis. However, existing models do not recapitulate cardiac-specific self-organizing patterning and morphogenesis to acquire in vivo-like architecture, and they are therefore limited as models of early human cardiogenesis and congenital heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…These have proven immensely useful to measure contraction force, perform compound screens and model structural muscle and arrhythmogenic disorders. Similarly, mouse and human PSC-derived 3D cardiac models including spherical aggregates (microtissues) of CMs and other cardiac cell types (Giacomelli et al, 2017;Richards et al, 2020), have been reported as promising tools for drug discovery; and embryoid models (Rossi et al, 2019;Silva et al, 2020) as providing insights into germ layer interactions in early organogenesis. However, existing models do not recapitulate cardiac-specific self-organizing patterning and morphogenesis to acquire in vivo-like architecture, and they are therefore limited as models of early human cardiogenesis and congenital heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fig.7. Analysis of single-cell RNAseq datasets from SBR Gastruloids highlights two "endoderm" clusters (A) Top: UMAP representation of the dataset fromRossi et al (2019). The two clusters attributed as "early endoderm" (13) and "mature endoderm" (4) are highlighted in gold and beige respectively.…”
mentioning
confidence: 99%
“…Upon administration of cardiogenic factors FGF, VEGF and ascorbic acid, mGastruloids reproducibly recapitulate cardiogenesis at their anterior end, giving rise a vascular-like network, first and second heart fields as well as ultimately a beating structure, resembling an actual embryonic heart [158]. Moreover, mGastruloids generated not only from mESCs but also from XEN cells exhibit increased cell type diversity and develop neural-tube-like structures.…”
Section: Mouse -Gastruloidsmentioning
confidence: 96%